Optihelp cuidado y protección para tu salud visual – Prototipo de una app (2022)
Visual hygiene habits have become very important due to the circumstances exposed by society due to the COVID-19 pandemic. for said confinement, without a doubt the work in near vision with devices technology, it has become a habit of daily use for most individuals, situation that due to the exponentially increased time to the use of these devices has caused effects on visual health (1).